The Doctrine of the Ordo Sclavoniae in Light of Western Sources and the Issue of the Origins of the Dualist Heresy in Bosnia - Czarnecki, Piotr (Studia Ceranea, 2022)
The issue of the Bosnian church – or more precisely the dualist heresy in Bosnia – has caused serious controversies among scholars since the 19th century. The main aim of this paper is to shed new light on this controversial issue, through the analysis of the doctrine of Slavonic dualism (ordo Sclavoniae) based on Western sources. The subject of the analysis will be the sources concerning the contacts of the Cathars from France and Italy with the heretics from Sclavonia and especially the sources containing information on the doctrine, such as the 13th-century Italian sources presenting the doctrines of the Cathars belonging to ordo Sclavoniae (Cathar churches of Bagnolo and March de Treviso) and later, 14th and 15th-century sources presenting the teachings of the heretics from Bosnia. The aim of the analysis will be to reconstruct the doctrines of Slavonic dualism (ordo Sclavoniae) in order to find its distinctive features (especially comparing with two main forms of Bogomil-Cathar dualism – Bulgarian and Drugunthian) and to answer the following question: which doctrinal conceptions had the most significant influence on its formation? Knowledge concerning the sources of inspiration for the dualist doctrine of the ordo Sclavoniae will enable us to draw conclusions concerning the origins of Slavonic dualism, its evolution and to assume an attitude towards scholars’ conceptions concerning the character of the Bosnian heresy.